Mediating role of green banking in enhancing non-financial performance: evidence from Indonesian commercial banks - Fangky A Sorongan; Steph Subanidja; Djoko Hanantijo; Mohammad Hidir Baharudin (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
This study investigates the mediating role of green banking in connecting sustainable organizational culture, green innovation capability, and bank reputation to the non-financial performance of Indonesian commercial banks. Although prior research largely emphasizes financial outcomes of green banking, its impact on non-financial dimensions such as operational efficiency, innovation, and reputation remains underexplored in emerging markets like Indonesia. A quantitative approach was employed, utilizing structural equation modeling (SEM) with AMOS on survey data from 270 respondents in the Indonesian banking sector. Findings show that green banking has a direct and significant positive effect on non-financial performance. Importantly, sustainable organizational culture, green innovation capability, and bank reputation affect non-financial performance solely through the full mediation of green banking practices. The results highlight that internal sustainability values and reputational assets yield no direct performance benefits unless embedded in concrete green banking initiatives. This underscores the need for banks to prioritize substantive implementation of sustainable products, eco-friendly operations, and regulatory compliance to gain competitive advantage in Indonesia’s green and digital economy.